Circulating tumour DNA (ctDNA) in metastatic melanoma, a systematic review and meta-analysis. (November 2021) - Gracie, Lara; Pan, Yi; Atenafu, Eshetu G.; Ward, Douglas G.; Teng, Mabel; Pallan, Lallit; Stevens, Neil M.; Khoja, Leila
Abstract: Introduction: : Circulating tumour DNA (ctDNA) is an emerging biomarker in melanoma. We performed a systematic review and meta-analysis to explore its clinical utility as a prognostic, pharmacodynamic (PD) and predictive biomarker. Methods: A systematic search was conducted from Jan 2015 to April 2021, of the electronic databases PubMed, Cochrane Library and Ovid MEDLINE to identify studies. Studies were restricted to those published in English within the last 5 years, evaluating ctDNA in humans in ≥10 patients. Survival data were extracted for meta-analysis using pooled treatment effect (TE), i.e. log hazard ratios (HRs) and corresponding standard error of TE for progression-free survival or overall survival differences in patients who were ctDNA positive or negative. PRISMA statement guidelines were followed. Results: A meta-analysis of 19 studies grouped according to methodology of ctDNA detection, revealed a combined estimate for HR of progression-free survival (13 studies using droplet digital Polymerase Chain Reaction (ddPCR) methodology (N = 1002) of 2.10 (95% CI: 1.71–2.59) revealing a poorer prognosis when ctDNA was detected. This result was confirmed in the smaller analysis of (non-ddPCR, N = 347) five studies: HR = 2.45 (95% CI: 1.29–4.63). Similar findings were found in the overall survival analysis of nine studies (ddPCR methodology, N = 841) where the combined HR was 2.78 (95% CI: 2.21–3.49) and of the five studies (non-ddPCR methodology, N = 326) where the combined HR was 2.58 (95% CI: 1.74–3.84). Serial ctDNA levels on treatment showed a pharmacodynamic role reflecting response or resistance earlier than radiological assessment. Conclusions: : Circulating tumour DNA is a predictive, prognostic and PD biomarker in melanoma. Technical standardisation of assays is required before clinical adoption. Highlights: ctDNA has prognostic and pharmacodynamic biomarker utility in advanced melanoma. Standardisation of analysis, data processing and reporting is needed. Standardization of methodology will enable clinical use for patient management.